Flotation of copper oxide minerals: A review - Feng, Qicheng; Yang, Wenhang; Wen, Shuming; Wang, Han; Zhao, Wenjuan; Han, Guang (International journal of mining science and technology, 2022)
Copper oxide minerals are important copper resources, which include malachite, azurite, chrysocolla, cuprite, etc. Flotation is the most widely used method for the enrichment of copper oxide minerals in the mineral processing industry. In this paper, the surface properties of copper oxide minerals and their effects on the mineral flotation behavior are systematically summarized. The flotation methods of copper oxide minerals and the interaction mechanism with reagents are reviewed in detail. Flotation methods include direct flotation (using chelating reagents or a fatty acid as collector), sulfidization flotation (using xanthate as collector), and activation flotation (using chelating reagents, ammonium/amine salts, metal ions, and oxidant for activation). An effective way to realize efficient flotation of copper oxide minerals is to increase active sites on the surface of copper oxide minerals to enhance the interaction of collector with the mineral surface. Besides, various perspectives for further investigation on the efficient recovery of copper oxide minerals are proposed.